ATTRACTING STUDENTS TO WORK AT GRANTS AS A FACTOR OF SHAPING SOCIAL AND PSYCHOLOGICAL COMPETENCE OF THE FUTURE SPECIALIST - Svetlana A. Ledneva (Вестник Российского экономического университета имени Г. В. Плеханова)
The article discusses a problem acute for present day professional education, i.e. the problem of using student's research work in university not only as professional but also as personal development of the future specialist. While the importance of the human factor for effective functioning of the organization is rising, special attention should be paid to the development of students' skills of social interaction. The author investigates the factor of social and psychological competence of the future specialist as a component of his/her successful interaction in the team. The article analyzes opportunities offered for the development of student's social and psychological competence by his/her cooperation with the lecturer in work at grants.